An injectable dosimeter for small animal irradiations. (17th September 2019) - Garty, Guy; Pujol-Canadell, Monica; Brenner, David J
Abstract: Accuracy and precision in dosimetry is crucial in studies involving animal models. Small animal dosimetry, in particular for protracted exposures to non uniform radiation fields is particularly challanging. We have developed a novel in vivo dosimeter based on glass encapsulated TLD rods. These encapsulated rods can be injected into mice and used for validating doses to an individual mouse in a protracted irradiation scenario where the mouse is free to move in an inhomogenous radiation field. Data from 30 irradiated mice shows a reliable dose reconstruction within 10% of the nominal delivered dose.